MATHEMATICS MIDDLE SCHOOL

drinking 6 fluid ounces of milk provides 202.5 mg of calcium how many fluid ounces of milk are required to provide 52.5 mg of calcium round to the nearest tenth

Answers

Answer 1
Answer:

Answer:

2 fluid ounces.

Step-by-step explanation:

202.5 divided by 6 = 33.75 (1 fluid ounce)


33.75 x 2 = 67.5.  (68)  








Related Questions

HIGH SCHOOL

What is the simplified form of the quantity of x plus 4, all over 5 + the quantity of x plus 5, all over 5? A.x2+9x+2
________
5
B.2x+9← I think is this one
______
5
C.x2+9x+20
________
25
D.x+4
____
x+5

Please help ASAP I am taking the exam right now!!!!!

Answers

Thats the right answer.
MIDDLE SCHOOL

What is the correct inverse function for f(x)=ln(3x)?

Answers

Answer:

Step-by-step explanation:

f(x)= ln(3x)

First we replace f(x) with y

y=ln(3x)

Now , interchange the variables x  and y

x= ln(3y)

Solve the equation for y

We know ln has base 'e'

e^x = 3y

divide by 3 on both sides


Let y = f(x)

y = ln(3x)

Exchange place with x and y.

x = ln(3y)

Solve for y.

y = (e^x)/3

Replace y with the inverse notation.

f^(-1) x = (e^x)/3

Done.



HIGH SCHOOL

Keisha spent 56$ on fruit at the grocery store. She spent a total of 80$ at the store. What percentage of the total did she spend on fruit?

Answers

56 is 70% of 80
so she spent 70% of her money of fruit
MIDDLE SCHOOL

Write the equation of the line with x-intercept 3 and passing through the point (5,4). Really Makes No Sense so I'd Like a Detailed Answer. Will give Brainliest

Answers

Answer:

The equation of the line is y = 2x - 6

Step-by-step explanation:

To find the equation of this line, we first need to find the slope. To find a slope you need two ordered pairs, which you have here. The first is (5, 4) and the second is (3, 0) - which is the x-intercept of 3. Now that we have this, we can plug into the slope equation.

m(slope) = (y2 - y1)/(x2 - x1)

m = (4 - 0)/(5 - 3)

m = 4/2

m = 2

Now that we have the slope, we can use that and either point in point-slope form. Once we do that, we solve for y to get the equation.

y - y1 = m(x - x1)

y - 4 = 2(x - 5)

y - 4 = 2x - 10

y = 2x - 6

Random Questions